PERANCANGAN VIDEO ANIMASI 2D DENGAN TEKNIK MOTION GRAFIK PADA INFORMASI PENERIMAAN MAHASISWA BARU UNIVERSITAS STIKUBANK (UNISBANK) SEMARANG (Information Technology and Telematics, 2015)
Abstract Strategic communication needs to be done by the College to communicate the brand towards external target, because the ultimate goal of brand communications College is affecting prospective students and parents in the process to make the decision of choosing universities. Both logos, names, colors, designs, slogans, buildings or facilities even the media used, need special attention. One medium of information that can be used to communicate the brand is media information using animation. With animation, the process of delivering the information will be more easily understood and understandable than using oral or written. With the media this information can help people who want to register as prospective students at Stikubank University (Unisbank) Semarang to find out information as well as the flow of new admissions application and selection process starting from registration, the admission test to the registration process. Through this research, will be made a 2D animation video using motion graphics technique that can provide information on new admissions and the flow of application and selection of new students at Stikubank University (Unisbank) Semarang. Keyword: 2D Animation, Motion Graphic